Rookie directors and firm performance: Evidence from China11We thank William L Megginson (the editor), two anonymous referees, Graeme Guthrie, Heng Geng, Adrian Cheung and seminar participants at the Victoria University of Wellington, Guangdong University of Foreign Studies and the 2018 Financial Market and Corporate Governance Conference. All remaining errors are our own - Chen, Zonghao; Keefe, Michael O’Connor (Journal of Corporate Finance, 2020)
This paper examines the benefits and costs associated with rookie independent directors (RIDs) in Chinese public companies from 2008 to 2014. We find that RIDs attend more board meetings. Boards with more RIDs tunnel less to controlling shareholders, suggesting that RIDs are efficient monitors. However, in state-owned firms, the presence of RIDs is negatively associated with investment efficiency, suggesting a potential cost of appointing RIDs. Overall, firms with more RIDs have higher operating performance, especially when tunneling is a more common issue, when board experience is less important and when monitoring costs are relatively low.